Species screening and multi-locational testing of Stylosanthes species in West Africa - Tarawali, Shirley A.; Peters, Michael; Jama, A.A. (International Livestock Centre for Africa, 1994)
The evaluation of Stylosanthes species has featured prominently in ILCA's forage evaluation programme in the subhumid zone of Nigeria. The evaluation of over 200 accessions within the genus using a series of evaluation stages ranging from small plot observation trials through to full-scale grazing trials is described. Accessions which are as good or better than S. hamata cv Verano, which is currently being used for pasture developments, included two S. guianensis accessions (ILCA 164 and 15557) and one S. hamata accession (ILCA 15876).